Stress‐Driven Failure of Cylindrical Volcanic Conduits. Issue 8 (21st August 2021) - Mullet, B. G.; Segall, P.
Abstract: Many explosive volcanic eruption sequences are characterized by exceedingly unsteady behavior, often punctuated by multiple explosive phases, separated by hours to days. What causes this unsteady behavior is not fully understood. Here, we explore one possible mechanism: stress‐driven failure of the volcanic conduit wall rock. We present a multiphase conduit flow model that predicts the shear and normal tractions exerted on the conduit wall, and couple (one way) these tractions with a numerical model of host rock failure. While analytical estimations of host rock stress serve as useful guides, analytical approximations which ignore shear tractions are insufficient to adequately predict conduit instability. Failure generally initiates near the fragmentation depth, where shear tractions are highest and magma pressure is low relative to the lithostatic stress. Shear tractions on the conduit wall, caused by viscous drag, promote strain localization and failure. The in situ stress state not only determines the range of conduit pressures which promotes failure, but also influences the style of failure. The mechanism that is most likely to lead to the disruption of flow, where wall rock moves radially into the conduit along normal faults, occurs in extensional stress regimes when large shear tractions at the fragmentation depth enhance normal fault formation. The results of this study indicate that conduit stability strongly depends on the ambient stress field and the nature of conduit flow at the fragmentation depth. Plain Language Summary: Explosive volcanic eruptions sometimes end abruptly. In this study, we explore one mechanism for abrupt termination of activity: the collapse of the volcanic conduit walls. We show that collapse of the volcanic conduit can occur when the ambient stress field is extensional and when the pressure in the volcanic conduit is low. Collapse is generally expected to occur at the fragmentation depth, where conduit pressures are low relative to the lithostatic stress. A number of other important factors, such as the shear stress exerted on the conduit wall by the flow of magma, are also examined. Our results indicate that the collapse of the volcanic conduit walls could be an important mechanism for understanding the temporal evolution of explosive eruptions. Key Points: Failure of the conduit wall rock can potentially explain the abrupt cessation of some explosive eruptions Failure depends on several factors, including in situ stress state, chamber pressure, and the fragmentation condition Models that properly account for the shear tractions exerted by viscous drag are necessary for accurate prediction of failure